2005
DOI: 10.1016/j.lungcan.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor pattern of expression in primary lung cancer and in normal human lung

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…For example, OT signaling inhibits the growth of ovarian, neuroblastoma, astrocytoma and other cell types (Cassoni et al, 2004). It was also reported that OXTR expression is reduced in approximately 50% of NSCLC tumors as monitored by immunohistochemistry, consistent with our findings (Pequeux et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…For example, OT signaling inhibits the growth of ovarian, neuroblastoma, astrocytoma and other cell types (Cassoni et al, 2004). It was also reported that OXTR expression is reduced in approximately 50% of NSCLC tumors as monitored by immunohistochemistry, consistent with our findings (Pequeux et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…AVP has been shown to induce a dose-dependent (from 1 nM) and time-persistent increase of tumor cell proliferation. V2 receptors are present in human breast cancer (47), cervical cancer (85), and lung cancer (95) cells and in corticotrophinomas, with V2Rs varying greatly, being lower in macroadenomas than in microadenomas (126). An abnormal truncated V2R was also detected in MCF-7 cells, although it appeared to be nonfunctional (87)(88)(89).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 99%
“…The presence of all AVP receptor subtypes, but particularly V2R, has been reported in transformed epithelial cells (86,89). V2R is present in a wide panel of human tumor cell lines, including human breast cancer cells (47), cervical cancer (85), lung cancer (95), and in corticotrophinomas (126).…”
mentioning
confidence: 99%
“…Recently oxytocin receptors have been found also in human airway smooth muscle [23]. Moreover, Amrani et al [24] have shown that asthma-related cytokines (IL-13 and TNF alpha) modulate the expression of oxytocin receptors in human airway smooth muscle function suggesting a potential role of inflammation-induced changes in oxytocin receptor signaling in the regulation of airway hyper-responsiveness in asthma.…”
Section: Background and Main Textmentioning
confidence: 99%